Slow and sudden violence: why and when uprisings occur - Hyra, Derek (University of California Press, 2024)
"In Slow and Sudden Violence, Derek Hyra weaves together a persuasive unrest narrative, linking police aggression to an ongoing cycle of racial and spatial urban redevelopment repression. By delving into the real estate history of the St. Louis region and Baltimore, Hyra shows how rounds of urban renewal decisions to segregate, divest, displace, and gentrify Black communities advance neighborhood inequality. Despite moments of racial political representation, repeated decisions to 'upgrade' the urban fabric and uproot low-income Black populations, result in Black poverty pockets inhabited by people experiencing chronic displacement trauma and unrelenting police surveillance. These interconnected sets of accumulated frustrations powerfully culminate and surface when tragic and unjust police killings occur. To confront the core components of U.S. unrest, Hyra suggests we must end racialized policing, stop Black community destruction and displacement, and reduce neighborhood inequality"-- Provided by publisher